Effect of Anesthesia/Surgery on Gut Microbiota and Fecal Metabolites and Their Relationship With Cognitive Dysfunction - Lian, Xinrong; Zhu, Qianmei; Sun, Li; Cheng, Yaozhong (Frontiers in Systems Neuroscience, 2021)
Aims: Postoperative cognitive dysfunction (POCD) is the decline in cognitive function of the central nervous system after anesthesia/surgery. The present study explored whether anesthesia/surgery altered gut microbiota and fecal metabolites, examining their associations with risk factors of cognitive dysfunction in aged mice. Methods: Sixteen-month-old C57BL/6 mice underwent abdominal surgery under isoflurane anesthesia to establish an animal model of POCD. The Morris water maze test (MWMT) was used as an indicator of memory after surgery. The effects of anesthesia/surgical interventions on gut microbiota, fecal metabolites, hippocampus, and serum levels of inflammatory factors were examined. Results: The anesthesia/surgery induced more serious POCD behavior, increasing brain IL-6 and IL-1β levels than sham control mice. The relative abundance of bacterial genera Bacteroidales_unclassified, Mucispirillum, and Clostridiales_unclassified declined, whereas that of Escherichia-Shigella, actinomyces, Ruminococcus_gnavus_group and Lachnospiraceae_FCS020_group were enriched after anesthesia/surgery compared to the baseline controls. Liquid chromatography-mass spectrometry (LC-MS) showed that the metabolites differed between post anesthesia+surgery (post_A+S) and baseline samples and were associated with the fecal metabolism of tryptophan, kynurenic acid, N-oleoyl γ-aminobutyric acid (GABA), 2-indolecarboxylic acid, and glutamic acid. Furthermore, the differential metabolites were associated with alterations in the abundance of specific bacteria. These results indicate that POCD intervention may be achieved by targeting specific bacteria associated with neurotransmitter metabolism. Conclusions: A transient cognitive disturbance induced by anesthesia/surgery may be associated with unfavorable alterations in gut microbiota and fecal metabolites, thereby contributing to POCD development. Keywords: gut microbiota, metabolomics, gut-brain axis, postoperative cognitive dysfunction, neurotransmitter